2021
DOI: 10.1007/s00264-021-04950-5
|View full text |Cite
|
Sign up to set email alerts
|

Injury characteristics and management of orthopaedic trauma in refugee children

Abstract: Purpose Several factors affect injury types in childhood. The aim of the study was to evaluate the musculoskeletal injury types, treatment modalities, and demographic characteristics of refugee children and to reveal the differences from native children. Methods A total of 1297 patients (897 females, 400 males) treated in our clinic between January 2014 and January 2019 were included in the study. The mean age of the patients was 8.9 ± 5.1 in refugees and 7.5 ± 4.6 in the native group (range, 0-18 years). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
5
2
Order By: Relevance
“…In our study, 20% of the trauma patients required mechanical ventilation, and there was no significant difference between the two groups in terms of mechanical ventilation need. In a trauma study conducted in Turkey, it was reported that hospitalization was longer in refugee children (17). However, there was no significant difference in the length to stay in PICU and hospital between the two groups included in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…In our study, 20% of the trauma patients required mechanical ventilation, and there was no significant difference between the two groups in terms of mechanical ventilation need. In a trauma study conducted in Turkey, it was reported that hospitalization was longer in refugee children (17). However, there was no significant difference in the length to stay in PICU and hospital between the two groups included in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…From this, we could infer that the preferred activities of older children shifted in favor of more sedentary activities such as the use of mobile phones and screens; at the same time, surgical indications have evolved. Young children (1–5 years) seemed to be more active and may have been more involved in physical activities in 2019 compared with 1999 [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology and distribution of pediatric fractures change over time and are influenced by a multitude of factors including geography, climate, and population characteristics such as lifestyle and demographics [ 1 , 2 , 3 ]. During the past two decades or so, dramatic demographic and socio-cultural modifications have influenced the epidemiology of pediatric fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most articles describing treatment of war victims focus either on a specific medical specialty [ 37 – 41 ], or on a certain group of diseases [ 8 , 42 48 ], commonly PTSD [ 14 , 49 ]. Surgical trauma case series are a special group of interest in the literautre [ 50 53 ].…”
Section: Discussionmentioning
confidence: 99%